Impact of Gypsum Application on the Methane Emission From a Wetland Rice Field - Denier van der Gon, H. A. C.; Neue, H.U. (American Geophysical Union, 1994)
Methane emission from Philippine rice paddies was monitored with a closed chamber technique during the 1991 and 1992 wet season. The methane emission from plots amended with 6.66 tons.ha−1 gypsum was reduced by 55–70% compared to non‐amended plots. Although CH4 emission from fields with a high input of fresh organic matter was strongly enhanced, the experiments showed that the relative reduction in CH4 emission upon gypsum application was independent of organic matter addition. The reduced CH4 emission upon gypsum application was most likely due to inhibition of methanogenesis by sulfate‐reducing bacteria. Observed SO42− concentrations in the soil solution of gypsum‐amended plots were well above minimum concentrations reported in the literature for successful competition of sulfate‐reducing bacteria with methanogens. The data provide a base for reducing the estimates of CH4 emissions from rice grown on high‐sulfate containing soils or gypsum‐amended soils.